Code Mixing Found in the Leonardo’s Podcast with Satria Mahatir - Permata, Made Goutamayasa; Sulatra, I Komang (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Nowadays, the use of two or more languages social media is a common phenomenon. This study aims to find out the types of Code Mixing in The Leonardo’s Podcast with Satria Mahatir and to analyze the reason of the usage of code mixing on The Leonardo's Podcast with Satria Mahatir. The data source of this study is The Leonardo's podcast with Satria Mahatir. This research method includes descriptive qualitative by means of observation, watching, and writing the utterances with code mixing data. The theory used in analyzing the data is according to Muysken (2000). The results of the findings, found that the type of code mixing are insertion, alternation, and congruent lexicalization. In the research carried out by the researcher, the number of code mixing found were 44 data which include insertion code mixing 40 data, alternation code mixing 3 data, and congruent lexicalization only 1 data. Insertion is used dominantly in the data source due to the lack of word equivalents and the influence of local prestige culture that can cause this to happen.